Design of a Mutual Exclusion and Deadlock Algorithm in PCBSD – FreeBSD - Caicedo Acosta, Libertad; Ospina Acosta, Camilo Andrés; Gelvez García, Nancy Yaneth; Romero Villalobos, Oswaldo Alberto (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This paper shows the implementation of mutual exclusion in PCBSD-FreeBSD operating systems on SMPng environments, providing solutions to problems like investment priority, priority propagation, interlock, CPU downtime, deadlocks, between other. Mutex Control concept is introduced as a solution to these problems through the integration of the scheduling algorithm of multiple queues fed back and mutexes.
Keywords: mutex; PcBSD; SMPng; freeBSD; operating systems; IJIMAI